Comparative Mitochondrial Genome Analyses of Sesarmid and Other Brachyuran Crabs Reveal Gene Rearrangements and Phylogeny - Li, Yue-Tian; Xin, Zhao-Zhe; Tang, Ying-Yu; Yang, Ting-Ting; Tang, Bo-Ping; Sun, Yue; Zhang, Dai-Zhen; Zhou, Chun-Lin; Liu, Qiu-Ning; Yu, Xiao-Min (Frontiers in Genetics, 2020)
Mitochondrial genomes (mitogenome) are important for understanding molecular evolution and phylogenetic relationships. The complete mitogenome of Perisesarma bidens was determined, which is 15,641 bp in length. The A+T content of P. bidens mitogenome was 74.81%. The AT skew was slightly negative (-0.021). The 22 tRNAs ranged from 65 to 73 bp and were highly A+T biased. All tRNA genes had typical cloverleaf structures, except for the trnS1 gene, which lacked a dihydrouridine (DHU) arm. The gene order within the P. bidens mitogenome was identical to the pancrustacean ground pattern, except for the translocation of the trnH. Additionaly, the gene order of trnI-trnQ-trnM in pancrustacean ground pattern became trnQ-trnI-trnM in P. bidens. Phylogenetic analyses supported the inclusion of P. bidens in Sesarmidae and the promotion of Sesarminae to Sesarmidae. The results will help us to better understand the status and evolutionary history of Grapsoidea crabs.